Walkable Area Within Which Destinations Matter: Differences Between Australian and Japanese Cities. (March 2015) - Sugiyama, Takemi; Inoue, Shigeru; Cerin, Ester; Shimomitsu, Teruichi; Owen, Neville
Adults' walking for transport is important for health benefits and can be associated with availability of destinations such as shops and services within a walking distance of 10 to 15 minutes from home. However, relevant evidence is mostly from Western countries. This study examined associations of destinations with walking for transport in Australian and Japanese cities. Data were collected from Adelaide, Australia (n = 2508), and 4 Japanese cities (n = 1285). Logistic regressions examined associations of self-reported walking for transport with the number of destination types within walk-distance categories. Walking was significantly associated with the number of destination types within a 10-minute walk from home for Australia and with the number of destination types within a 6- to 20-minute walk for Japan. Further research is needed on why walking by residents of Japanese cities can be influenced by more distant local destinations than in Australia to inform physical activity–related environmental and policy initiatives.